PENETAPAN TERAPI RENDAM KAKI AIR HANGAT JAGA (ZINGIBER) TERHADAP PENURUNAN NYERI DI WILAYAH KERJA TIBAN BARU KOTA BATAM - Khanza Aqilah; T Eltrikanawati T Eltrikanawati (Ensiklopedia of Journal, 2025)
Hypertension or high blood pressure is a chronic condition characterized by increased blood pressure on the walls of the arteries. Hypertension can cause degenerative disease, even death, which is why hypertension is nicknamed the silent killer or a silent killer that can attack anyone and has no specific signs. The number of sufferers in 2022 will be 235,689 cases. The largest number of hypertension sufferers was at the Sei Langkai Community Health Center with 16,394 cases (Riau Islands Health Service, 2022). This professional scientific paper aims to provide medical surgical nursing care for Mrs. Descriptive with a case study approach carried out based on the stages of nursing care including assessment, diagnosis, intervention, implementation and nursing evaluation. The results of the Professional Scientific Writing work were obtained when the client complained of pain with a pain scale of 6 to 2 on the first day with a pain scale of 6, the second day the pain scale was 4 and the third day the pain scale was 2 after the warm ginger water foot soak therapy. This therapy can be a non- pharmacological treatment to reduce pain in hypertension sufferers.Keywords : Hypertension, Nursing Care, Soak feet in warm ginger water